Understanding Usability Test of Operating Systems in University: Evidence from Indonesia - Muyu, Ronaldo; Poluakan, Christy; Yeremia, Undap E.B (International Journal of Information Technology and Education, 2022)
The operating system is the most important computer system software. Currently, there are several operating systems that are so popular, including Windows and macOS. Usability measurements were made between the Windows and macOS operating systems. This study aims to measure the comparison of usage between Windows and Mac operating systems in lectures at the University. This study used a questionnaire with 13 questions asked and 250 respondents received, then analyzed the data using a Guttman measuring scale. The results show that the Windows operating system is more widely used with a much higher percentage than MacOS. The results of this study also prefer the Windows operating system with 84.61% while MacOS with 11.38%. Because starting in terms of popularity among university students, many use Windows because it is considered easier and the applications provided for free are different from prepaid MacOS